2012
DOI: 10.1140/epjd/e2012-30228-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical radiative properties of odd-parity highly excited levels in Mo II

Abstract: Abstract. Radiative lifetimes of 13 odd-parity levels of Mo II have been measured using time-resolved laser-induced fluorescence (TR-LIF) spectroscopy in a plasma produced by laser ablation. The investigated levels, within the energy range 48 022−63 497 cm −1 , were excited from the ground or appropriate metastable states with one-photon selective excitation. The uncertainties of the measured lifetime results are less than 10%. Calculated lifetimes of Mo II, obtained using the relativistic Hartree-Fock (HFR) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 16 publications
(24 reference statements)
1
22
0
Order By: Relevance
“…In practice, this parameter is usually chosen to be equal to the HFR mean value < r > for the outermost ionic core orbital. When looking at Table 1 , one can observe that ab initio HFR radial dipole integrals are about 20% larger than the values extracted from our oscillator strength parametrization (OSP) approach while the difference is reduced to a few percent when considering the HFR + CPOL results obtained using a Mo IV ionic core, as reported in [10,11] . In the same Table, for further analysis, we have also added HFR and HFR + CPOL radial integral values for transitions involving the 4d 3 5s5p configuration.…”
Section: Oscillator Strength Calculationmentioning
confidence: 83%
See 2 more Smart Citations
“…In practice, this parameter is usually chosen to be equal to the HFR mean value < r > for the outermost ionic core orbital. When looking at Table 1 , one can observe that ab initio HFR radial dipole integrals are about 20% larger than the values extracted from our oscillator strength parametrization (OSP) approach while the difference is reduced to a few percent when considering the HFR + CPOL results obtained using a Mo IV ionic core, as reported in [10,11] . In the same Table, for further analysis, we have also added HFR and HFR + CPOL radial integral values for transitions involving the 4d 3 5s5p configuration.…”
Section: Oscillator Strength Calculationmentioning
confidence: 83%
“…Eighteen years later Sikström et al [9] reported experimental branching fraction values, ranging in the wavelength from 1970 to 4370 Å and radiative lifetime measurements for 10 levels. We have to mention also the complementary extensions on the same subject, done by Lundberg et al [10] and Jiang et al [11] . Recently a Spanish team has presented numerous new oscillator strength measurements, arising mainly from highly excited levels [12,13] .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the case of Mo II, an extensive analysis of a Fourier transform spectrum has been carried out by Nilsson and Pickering [34], who added 110 new levels to those in previous work by Kiess [35]. Measurements and calculations of lifetimes and transition probabilities have been made by Jiang et al [36], Lundberg et al [37], Sikstrom et al [38], Schnehage et al [39], and Hannaford and Lowe [40].…”
Section: Introductionmentioning
confidence: 99%
“…The present work can be seen as an extension of our recent investigations of the fifth row elements Y II, Y III [5], a e-mail: pascal.quinet@umons.ac.be Zr II [6], Nb I [7], Nb II, Nb III [8], Mo II [9][10][11], Tc II [12], Ru I [13], Ru II, Ru III [14], Rh II [15,16], Rh III [17], Pd I [18], Pd III [17], Ag II [19,20], Ag III [17], Sn I [21][22][23], Sb I [24], Te II and Te III [25].…”
Section: Introductionmentioning
confidence: 99%